Re-Audit of Discontinuation Plans on Discharge for Prescribed Hypnotics in General Adult Inpatient Services - Rifat Binte Radwan; Aamir Mujtaba (BJPsych Open)
Aims: Assess the number of patients discharged from General Adult Psychiatry wards with hypnotics prescribed for insomnia.